Variant Creutzfeldt-Jakob Disease. Issue 1 (1st October 2001) - Lowman, Andrea; Knight, Richard; Ironside, James
Abstract : INTRODUCTION Creutzfeldt–Jakob Disease (CJD) has been the focus of much attention in recent years due to the identification of a new variant now known as variant CJD (vCJD). Experimental evidence has shown that vCJD is due to human infection with the causative agent of Bovine Spongiform Encephalopathy (BSE), which was epidemic in UK cattle in the 1980s and early 1990s. Although vCJD remains rare, its existence has many implications. Clinicians have to face many questions from patients, relatives and other health care professionals. This review aims to present some of the scientific background, help health care professionals recognize the typical clinical picture and thus aid diagnosis. CJD is a human transmissible spongiform encephalopathy (TSE). Uniquely, it is a disease that exists in sporadic, inherited and infectious forms. It is a rare, invariably fatal neurodegenerative disease that can be difficult to diagnose during life, and neuropathological examination of the brain